Tax policy issues in OECS countries - Lewis, Wilfred (CDB WildeyBB, 1987)
Discusses levels of taxation and requirements of a good tax system such as equity, administrative ease and economic efficiency. Highlights need for marginal improvements in reforming tax systems. Discusses regional issues such as fiscal incentives, harmonization of corporation income tax, and customs administration.